Astrazeneca equity research - big pharma on the brink of future changes in oncology - Kerkow, Jonas Karl (2022)
The pharmaceutical industry is distinguished by a highly competitive market. Furthermore, various growth trends provide promising outlooks for the future development of the sector. Thus, competitors need to focus on measures such as strong R&D spending to be able to defend their positioning in the industry. These prospects compose the basis for further expansion while we assess two possible outcomes.